System architecture information decision support - Додонов, О. Г.; Ланде, Д. В.; Коваленко, Т. В. (Problems of Informatization and Control, 2015)
Presented by technological and methodological bases of creation and application of decision supportbased on the scenario approach, system architecture promoted, creation and use of ontologies forbuilding plots Information counter. Detailed analytical study of the technique based on the use of toolsof analysis and visualization of data flows and time series. These architectural solutions can be usedin systems based on the use of content-monitoring information space and scenario analysis, as well asanalytical and forecasting activities